The elephant in the universe our hundred-year search for dark matter - Schilling, Govert (The Belknap Press of Harvard University Press, 2022)
"If existing models of the structure of the universe are correct, then 85 percent of the cosmos comprises a substance called dark matter. Yet no direct evidence of dark matter exists. Award-winning science journalist Govert Schilling details the quest to detect dark matter and how the search has helped us to understand the universe we inhabit"--